2017
DOI: 10.1080/2162402x.2017.1330235
|View full text |Cite
|
Sign up to set email alerts
|

NK cell dysfunction in chronic lymphocytic leukemia is associated with loss of the mature cells expressing inhibitory killer cell Ig-like receptors

Abstract: A prospective analysis of natural killer (NK) cell phenotype and function was performed on fresh peripheral blood samples from untreated patients with B-cell chronic lymphocytic leukemia (CLL) or small lymphocytic lymphoma (SLL). Compared to healthy controls, CD56 dim NK cells in CLL patients displayed reduced expression of the NKG2D activating receptor and increased CD27 expression, which indicates declines in mature cells. In addition, NK cells from CLL patients showed reduced degranulation responses toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 66 publications
1
63
0
1
Order By: Relevance
“…Functional and phenotypic impairments of NK cells have been reported in a variety of solid and hematologic malignancies, including CLL [10, 35]. Dysregulation and imbalance of activating and inhibitory NK cell receptors could be one of the main reasons for NK cell impairment in CLL [36]. The results from the present study revealed that NK cells of CLL patients express higher levels of Tim-3 and lower levels of NKp30 in comparison to those of healthy individuals.…”
Section: Discussionsupporting
confidence: 62%
“…Functional and phenotypic impairments of NK cells have been reported in a variety of solid and hematologic malignancies, including CLL [10, 35]. Dysregulation and imbalance of activating and inhibitory NK cell receptors could be one of the main reasons for NK cell impairment in CLL [36]. The results from the present study revealed that NK cells of CLL patients express higher levels of Tim-3 and lower levels of NKp30 in comparison to those of healthy individuals.…”
Section: Discussionsupporting
confidence: 62%
“…In contrast to CD8 1 T cells, NK cell cytokine production and degranulation are impaired in untreated CLL patients. 17,18 Following venetoclax-obinutuzumab treatment, degranulation, as well as IFN-g production, of NK cells improved significantly ( Figure 4G).…”
Section: Tumor-supportive T-cell Subsets Decline During Venetoclax-obmentioning
confidence: 98%
“…[13][14][15][16] NK cell functionality is also impaired in CLL, particularly with regard to degranulation and cytotoxicity. 17,18 Similar to other B-cell lymphomas, such as follicular lymphoma, the lymph node (LN) microenvironment in CLL is thought to be the predominant site of interaction between the malignant cells and tumor-associated and tumor-specific immune cells. 19 However, data on immune abnormalities in CLL patients are primarily obtained from peripheral blood (PB) studies, and little is known about the composition of nonmalignant lymphocytes in LN tissue or how this relates to PB.…”
Section: Introductionmentioning
confidence: 99%
“…TriKE 161519 was recently described by Felices et al (271) for treatment of chronic lymphocytic leukemia (CLL); this antibody consists of anti-CD19 and anti-CD16 fragments, with an additional IL-15 moiety. Inclusion of the IL-15 moiety may be beneficial in CLL patients, who display low numbers and survival of mature and functional NK cells (272). TriKE 161519 induced superior NK cell activity against lymphoma cell lines and primary CLL patient cells compared to Rituximab, and, importantly, promoted NK cell survival and proliferation.…”
Section: Engagers Of Nk Cells To Unleash Nk Cell Activitymentioning
confidence: 99%